“Soldados da borracha” – esquecidos ou não lembrados? - PEREIRA, Gilson Laone (Universidade Federal do Pará, 2020)
This article proposes an interpretation on the way of life of the “soldiers of the rubber”, which were Brazilians who had acted in the Second World War. They were recruited by the Brazilian government, which is taking advantage of the problems faced by northeasterners; recruit thousands of them to go to the Amazon working on the extraction of latex, which would be exported to the United States to support the government and its allies in the war. With the entry of the Americans in the war, and with the taking of Malaysia by Japan, who was with the hegemony of the rubber during that period, Brazil was the only one able to provide this material. Within the performance Brazilian in Second War were on the scene over 70 thousand soldiers, about 25,000 members of the Brazilian Expeditionary Force and a little more than 55,000 soldiers who served in the extraction of latex. By means of material culture can identify information on the way of life for the soldiers of the rubber in the rubber plantations in the north of Brazil, It confirmed the intense adversity found.